2020
DOI: 10.1002/adma.202000006
|View full text |Cite
|
Sign up to set email alerts
|

2D Electrets of Ultrathin MoO2 with Apparent Piezoelectricity

Abstract: Since graphene, a variety of 2D materials have been fabricated in a quest for a tantalizing combination of properties and desired physiochemical behavior. 2D materials that are piezoelectric, i.e., that allow for a facile conversion of electrical energy into mechanical and vice versa, offer applications for sensors, actuators, energy harvesting, stretchable and flexible electronics, and energy storage, among others. Unfortunately, materials must satisfy stringent symmetry requirements to be classified as piezo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 55 publications
(78 reference statements)
2
39
0
Order By: Relevance
“…These transient and extreme ultrasonic cavitation pressure waves can cause massive PTFE deformation resulting in permanent structural defects. As a consequence, the concurrent electric fields can generate charges that can be trapped in the PTFE structural defects creating an electret state 26 . In addition, although the initial PTFE as a whole is centrosymmetric, some of the local regions near these chemical or physical defects may cause PTFE to be in a localized noncentrosymmetric phase 35 .…”
Section: Resultsmentioning
confidence: 99%
“…These transient and extreme ultrasonic cavitation pressure waves can cause massive PTFE deformation resulting in permanent structural defects. As a consequence, the concurrent electric fields can generate charges that can be trapped in the PTFE structural defects creating an electret state 26 . In addition, although the initial PTFE as a whole is centrosymmetric, some of the local regions near these chemical or physical defects may cause PTFE to be in a localized noncentrosymmetric phase 35 .…”
Section: Resultsmentioning
confidence: 99%
“…Some 2D monolayer transition metal dichalcogenides such as MoS2, MoTe2, WTe2, and MoO2, are piezoelectric. [219][220][221] Specially, monolayers of post transition metal mono-chalchogenides, such as SnS, show very high piezoelectric coupling coefficients. 222 A precise control of the liquid flow is important in biosensing to direct the analytes onto the surface of 2DMs.…”
Section: Perspectives For Virus Detectionmentioning
confidence: 99%
“…Piezoelectric materials allow conversion of mechanical energy into electrical energy and vice versa. Some 2D monolayer transition metal dichalcogenides such as MoS 2 , MoTe 2 , WTe 2 , and MoO 2 are piezoelectric. Specially, monolayers of post-transition metal mono-chalcogenides, such as SnS, show very high piezoelectric coupling coefficients …”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
“…Ajayan et al confirmed that the out‐of‐plane piezoresponse value was 0.56 pm V − 1 for 2D ultrathin MoO 2 . [ 65 ] Extended piezoresponse and Kelvin probe force microscopy (KPFM) studies were conducted on the flakes to alleviate the chance of seeing hysteresis as a result of charge injection from the PFM tip. Zhang et al reported that a typical butterfly amplitude loop was obtained with a sudden phase change from 30 o to 210 o by a sweeping DC voltage from −28 to +28 V, suggesting the local switching of the ISPEF induced by ferroelectric polarization of KNbO 3 nanosheets (NS).…”
Section: Experimental Characterizations Of Ispefmentioning
confidence: 99%